Strengthening Teacher Professionalism Trough The Educational Staff Internship Program - Wahyuni, Atika; Lia Nata Syafitri; Husinsah (Yayasan Insan Cipta Medan, 2024)
To become a professional teacher requires intensive and continuous training. This training includes the development of pedagogical skills, mastery of materials, and the ability to adapt to educational developments. This training can be followed through the educational staff apprenticeship program. This study aims to analyze the strengthening of teacher professionalism through the educational staff apprenticeship program which has an impact on the quality of a teacher. This research uses a descriptive qualitative approach using observation and interview methods. The results of this study indicate that the competence of education teachers in developing the competence of teacher professionalism through the educational staff internship program in one of Junior High School in Medan has experienced development. The educational personnel internship program plays an important role in teacher professionalism. Through this development, high school teachers in Medan city should be able to take an important part in achieving their duties and responsibilities as a teacher.